Associated Risk Factors of Chronic Kidney Disease in Jalalabad Afghanistan - Azimee, Mohammad Azim; Zafarzai, Imran; Sherzad, Abdul Ghafar; Zaheer, Shafiullah (International Journal For Research In Biology & Pharmacy, 2020)
BACKGROUND: Chronic kidney disease is a global health problem, affecting the majority of countries in the world. Its prevalence is approximately 10% and is associated mainly with Diabetes mellitus and hypertension. It is a condition in which the kidneys function or structural changes or GFR is reduced from / 1.7 sq.m 60ml / min for three months or longer and it is the leading cause of death in hospitals after cardiovascular disease, tuberculosis and malaria. OBJECTIVES: Determine the Risk factors of chronic kidney disease, such as age, sex, Family history, Drug use, smoking, and socioeconomic status, and concurrent Disease, such as hypertension and Diabetes mellitus associated with chronic renal insufficiency. METHODS: This is a Descriptive cross-sectional study conducted in Nishtar National Kidney and Rukhan Teaching Hospitals Jalalabad, Afghanistan, and was performed on 103 patients under Hemodialysis Departments from March through December 2019 and collect data from Individual health histories, Demographic characteristics (age, sex, Body weight, Height, Place of Residence and others factors) on social conditions and risk factors. A physical examination was performed, along with laboratory tests (blood chemistry) to measure renal function and detect markers for renal damage, the history of certain diseases and the presence or absence of certain habits have been investigated. RESULT: The study included a total of 103 patients with chronic renal insufficiency. 61 (59.2%) were Males and 42 (40.8%) females with no significant difference in the number of gender. The majority of the patients were men and residents of Nangarhar province with an average age of (Mean± SD) 40.53 ± 18.06 years. The majority of patients were married, illiterate and of mid-level socioeconomic status. Three out of every four patients with renal insufficiency had a history of high blood pressure, as well as kidney stones, Diabetes mellitus and Dyslipidemia. In terms of habits, the use of other types of tobacco (such as naswar), smoking and the use of certain drugs have been found to be very addictive. CONCLUSIONS: Chronic kidney Disease is alarming in communities, among both young and older age, men and women. Health services must be properly aligned to manage increased burden of chronic kidney disease, and preventive strategies should be implemented in a practical way.